Magnetic Resonance-Guided Focused Ultrasound Thalamotomy for Essential Tremor Under General Anesthesia: Technical Note. Issue 4 (11th April 2022) - Mensah-Brown, Kobina G.; Yang, Andrew I.; Hitti, Frederick L.; Henry, Lenora; Heman-Ackah, Sabrina M.; Chaibainou, Hanane; Baltuch, Gordon H.
Abstract : BACKGROUND: Magnetic resonance–guided focused ultrasound (MRgFUS) thalamotomy is an incisionless therapy for the treatment of medication-resistant essential tremor. Although its safety and efficacy has been demonstrated, MRgFUS is typically performed with the patient awake, with intraprocedural neurological assessments to guide lesioning. OBJECTIVE: To report the first case of MRgFUS thalamotomy under general anesthesia in a patient whose medical comorbidities prohibit him from being in a supine position without a secured airway. METHODS: The dentatorubrothalamic tract was directly targeted. Two sonications reaching lesional temperatures (≥54°C) were delivered without any complications. RESULTS: Lesioning was confirmed on intraoperative magnetic resonance imaging, and the patient experienced 89% improvement in his tremor postoperatively. CONCLUSION: This demonstrates the safety and feasibility of MRgFUS thalamotomy under general anesthesia without the benefit of intraprocedural neurological assessments.